L.A. confidential [videorecording (DVD)] - Hanson, Curtis; Spacey, Kevin; Crowe, Russell, 1964-; Basinger, Kim, 1953-; Ellroy, James, 1948- (Warner Home Video, 1998)
Three detectives in the corrupt and brutal L.A. police force of the 1950s use differing methods to uncover a conspiracy behind the shotgun slaying of the patrons at an all-night diner. A tribute to tough film noir crime films.